Islamic Law Overview on The Cashback System and The Use of Shopee Coins in Buying Transactions in The Shopee Application - Alfan Syafi'i; Dina Madinah; Dedeh Nurdaimah (Journal of Applied Business, Taxation and Economics Research, 2021)
This study uses a descriptive qualitative method because it describes the data in the form of a written description. Types and sources of data in this study using primary and secondary data. Data collection techniques through interviews, observation, and documentation. The data obtained in this study are conclusions from various processes in qualitative research. Starting from data collection, selecting appropriate data, presenting data and then concluding.The results of this study are in a review of Islamic Law, the provision of cashbacak promos by shopee parties to users is limited to giving gifts, as a marketing strategy to attract as many customers/users of the application as possible. And the use of shopee coins as discounted prices in buying and selling transactions is allowed, because the shopee coins used are obtained from cashback at the time of the previous transaction and the cashback is allowed.